The role of antenatal vitamin e supplementation in the prevention of neonatal jaundice. - Jaafar, Rohana; Abdullah Mahdy, Zaleha; Siraj, Harlina Halizah; Khaza'ai , Huzwah; Abd Mutalib, Mohd Sokhini; Mohd Dali, Ahmad Zailani Hatta (IOS Press, 2010)

(untitled)
Objective: To determine the effect of maternal antenatal vitamin E supplementation on neonatal jaundice.